Towards propagation of epidermal cells for wound repair: glass, as cell culture substrate, enhances proliferation and migration of human keratinocytes - Shahin, Hady; Steinvall, Ingrid; Sjöberg, Folke; Elmasry, Moustafa; El-Serafi, Ahmed (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionHuman keratinocytes require relatively long propagation time which impedes their availability as autologous cell transplantation within a clinically reasonable timeframe. There is an unmet need for efficient xeno-free cell expansion approaches to propagate human keratinocytes as regenerative therapy.MethodsPrimary human keratinocytes and HaCaT cells were cultured on glass, plastic, and animal-derived collagen I matrix for 10 days. Proliferation, migration, DNA methylation, as well as gene and protein expression were assessed to characterize the effect of the tested culture substrates on keratinocytes at the molecular and functional levels.ResultsKeratinocytes cultured on glass exhibited faster proliferation, global DNA demethylation and upregulation of epidermal differentiation markers. Scratch wound assay revealed that keratinocytes cultured on glass demonstrated enhanced cell migration compared to those on plastic or collagen I. Multiplex immunoassays identified temporal and substrate-dependent variations in a panel of keratinocyte-specific secreted factors, encompassing immunomodulatory cytokines, growth factors, and angiogenic factors.DiscussionGlass, as a culture substrate, promotes epidermal differentiation and enhances keratinocyte migration. The latter is a critical factor in re-epithelialization and wound healing. Functional properties suggest that glass may optimize the inflammatory response and promote efficient wound repair, making it a promising candidate for the short-term expansion of keratinocytes for transplantation purposes. Further in-vivo validation is required to definitively establish the efficacy of keratinocytes cultured on glass for clinical applications.